The effectiveness of using kids song to teach listening on young learner viewed from students' motivation at azhar tahfidz - Tauricha Astiyandha; Chusnul Chotimah (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
This study aims to investigate the effectiveness of using kids songs to teach listening on young learner viewed from students’ motivation at Azhar Tahfidz. The importance of implementing songs in teaching English as a second language (ESL) showing that they can be very effective in developing student’s listening. By using kids song, students are expected to understand more in listening. Song are appreciated for their linguistic, cultural and entertaining features and they are precious language learning materials. They can be used to teach and develop every aspect of language. This paper deals with theoretical explanations of young learner listening skills. It also discusses how songs can influence motivation for English language listening. The participants were two differents groups from AzharTahfidz. Their motivation was examined with and without implementing song. Analysis of the data using a t– test suggested that using songs in teaching English for young learners was significantly effective in raising their motivation to learn the language. The participants were students of fourth grade. In total, they were 28 students divided into two groups 14 students in a control group and 14 in an experimental group. They were almost at the same age 9 years old. They were 9 males and 5 females in the control and 8 males and 6 females in the experimental group.